Proceedings of the 35th IEEE/ACM International Conference on Automated Software Engineering 2020
DOI: 10.1145/3324884.3416543
|View full text |Cite
|
Sign up to set email alerts
|

Understanding performance concerns in the API documentation of data science libraries

Abstract: The development of ecient data science applications is often impeded by unbearably long execution time and rapid RAM exhaustion. Since API documentation is the primary information source for troubleshooting, we investigate how performance concerns are documented in popular data science libraries. Our quantitative results reveal the prevalence of data science APIs that are documented in performance-related context and the infrequent maintenance activities on such documentation. Our qualitative analyses further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Maintainability. Maintainability includes studies that are related to the process of correcting errors or conflicts found in API documentations (e.g., [21,42,43,56,61,71,72,73,74,81,83,86,104,105,106,107]). The improvement of API documentation maintenance has been explored in two areas.…”
Section: Quality Dimensions For Api Documentationmentioning
confidence: 99%
“…Maintainability. Maintainability includes studies that are related to the process of correcting errors or conflicts found in API documentations (e.g., [21,42,43,56,61,71,72,73,74,81,83,86,104,105,106,107]). The improvement of API documentation maintenance has been explored in two areas.…”
Section: Quality Dimensions For Api Documentationmentioning
confidence: 99%
“…2) Solver: This parameter has five solvers which are lbfgs, liblinear, sag, saga, and newton-cg. Liblinear is a decent choice for small datasets, while sag and saga are quicker for big ones [38]. Only lbfgs, sag, newton-cg, and saga can handle multinomial loss in multiclass issues.…”
Section: ) Penaltymentioning
confidence: 99%
“…Overall, a blockchain-based semantic exchange framework for Web 3.0 can facilitate the development of a participatory economy by enabling decentralized, peer-to-peer transactions without intermediaries. [4] This can help to reduce transaction costs, increase transparency, and enable greater participation in economic activities.…”
Section: Introductionmentioning
confidence: 99%